Strategi Kebijakan Penambangan Pasir Besi di Kabupaten Cianjur - Muhsin, Muhsin; Hidayat, Aceng; Putri, Eka Intan Kumala (Universitas Brawijaya, Indonesia, 2016)
Iron sand is the one of mineral mining products that produced by Cianjur District. Products are marketed from mining is generally still a raw material,it is an impact on the company's profits that not optimal and lower government revenues.Mining activities have also resulted in damage to the roads by trucks that transporting iron ore.Based on the analysis by matrix, the internal-external (IE) factor on the SWOT analysis is known that iron sand mining activities in Cianjur is in cell 5. It means that iron sand mining activities in Cianjur required strategic of growth or stability. With AHP analysis, the researcher obtained alternative strategies iron sand mining in Cianjur. Construction of the smelter enterprises become the main alternative to increase government revenue, mining bussiness profit and welfare of miners. Transportation of goods by sea became the main alternative to preserve the environment and infrastructure.